KORELASI ENZIM LAKTAT DEHIDROGENASE DENGAN DERAJAT INFEKSI DENGUE PADA PASIEN ANAK - Kunti Dewi Saraswati; Christina Roosarjani; Antony Halim Gunawan (Jurnal Infokes, 2019)
Introduction: Dengue infection is an acute febrile illness, caused by the virus species Flaviviridae. Liver damage and an increase in liver enzymes, due to the direct effect of the virus on the liver cells or the body's immune response against the virus.The presence of non-neutralizing antibodies that form the antibody virus complex causes enhancement of DEN virus infection, stimulates activated macrophages, secretes IL-1, IL-6, TNF alpha, and Platelet Activating Factor.This affects the vascular endothelium resulting in plasma leakage. The purpose of this study was to determine the correlation between lactate dehydrogenase levels and the degree of dengue infection.Method: Retrospective of child hemorrhagic infection patients. Data obtained from medical records. Correlations were analyzed with Spearman (p <0.05 = significant). Results: From 36 subjects, 21 men (58.3%), 15 women (41.7) were found. A total of: 16 (44.4%), 15 (41.7%), 3 (8.3%) and 2 (5.6%) subjects respectively were DHF degrees I, II, III, IV with LDH mean grade I (673.0 + 192.9u / l), grade II (782.9 + 188.7 u / L), grade III (909.3 + 428.2 u / l), grade IV (1118.0 + 110.3 u / l).Conclusion: Patients with pediatric dengue infection need to have liver enzymes examined to evaluate liver damage. Further research is recommended with a larger sample size.